The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1128/jb.01546-10
|View full text |Cite
|
Sign up to set email alerts
|

The Sensor Kinase KinB Regulates Virulence in Acute Pseudomonas aeruginosa Infection

Abstract: Two-component sensors are widely used by bacteria to sense and respond to the environment. Pseudomonas aeruginosa has one of the largest sets of two-component sensors known in bacteria, which likely contributes to its unique ability to adapt to multiple environments, including the human host. Several of these two-component sensors, such as GacS and RetS, have been shown to play roles in virulence in rodent infection models. However, the role and function of the majority of these two-component sensors remain un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 58 publications
2
50
0
1
Order By: Relevance
“…Our virulence data with BALB/c mice corroborate the recent observation that kinB controls virulence in PA14 against zebrafish embryos (7). In addition to the phenotypes described here, others have shown that KinB regulates pyocyanin, elastase, and biofilm formation (7). Here, we also observed increased expression of elastase (lasB) ( Tables 2 and 3).…”
Section: Figsupporting
confidence: 67%
See 2 more Smart Citations
“…Our virulence data with BALB/c mice corroborate the recent observation that kinB controls virulence in PA14 against zebrafish embryos (7). In addition to the phenotypes described here, others have shown that KinB regulates pyocyanin, elastase, and biofilm formation (7). Here, we also observed increased expression of elastase (lasB) ( Tables 2 and 3).…”
Section: Figsupporting
confidence: 67%
“…Here, we also observed increased expression of elastase (lasB) ( Tables 2 and 3). Interestingly, the authors of the aforementioned study showed that the kinase activity of KinB was dispensable for virulence (7). Collectively, these data indicate control of the KinB regulon is pleiotropic and complex.…”
Section: Figmentioning
confidence: 79%
See 1 more Smart Citation
“…Interestingly, we found that KinB's regulation of acute virulence phenotypes is independent of its kinase activity, since a kinase-inactive mutant of KinB regulates acute virulence phenotypes similarly to wild-type KinB. Moreover, we found that deletion of algB, the gene encoding KinB's cognate response regulator, also resulted in acute virulence phenotypes similar to those of wild-type PA14 (7). Thus, we proposed that KinB regulates these phenotypes in a noncanonical manner.…”
mentioning
confidence: 57%
“…It was shown that in addition to alginate synthesis down-regulation, KinB seems to control a large number of genes coding for virulence factors that are important to the development of acute pneumonia and causes a switch between chronic and acute infection (9,10). KinB also appears to be essential in acute infections in zebrafish embryos and other virulence-associated phenotypes, such as quorum sensing, biofilm formation, and motility (11). These phenotypes, however, are independent of KinB's kinase activity and its response regulator AlgB, indicating an atypical, noncanonical TCS signaling mechanism (10).…”
mentioning
confidence: 99%